A Study on the Behavior of Cutting One's Thigh Flesh for Healing in Beijing Local Chronicles during the Ming and Qing Dynasties - Han ZHANG; Zhuo CHEN; Jing ZHANG; Xinren ZHAO; Jiao WU; Lingzhi SUN (Yixue yu zhexue, 2025)
This article is based on the local chronicles of Beijing, and studies the phenomenon and motivations behind self-mutilation for healing (cutting one's thigh flesh to heal sick relatives) during the Ming and Qing dynasties. The findings reveal that this practice was widespread across social classes, affecting both impoverished and elite families, with women being the most impacted. Folk healers and unqualified physicians contributed to the spread of this behavior. Beyond serving as psychological comfort for families of the ill, self-mutilation was largely an uncritical extension of the use of human-derived substances in Traditional Chinese Medicine. Government commendations for those who performed such acts added moral and political significance, elevating the practice beyond medical treatment and intertwining it with rituals and mystical beliefs, reinforcing its deep-rooted folk nature. Today, a dialectical approach to understanding this phenomenon is essential for gaining a correct perspective on the historical use of human-derived substances in medicine.